Differentiation of human pluripotent stem cells into insulin-producing islet-like clusters using nanofiltered cell culture medium - Thorngren, Julia; Vasylovska, Svitlana; Blanc, Jules; Wu, Lulu; Manukyan, Levon; Mihranyan, Albert; Lau, Joey (Frontiers in Membrane Science and Technology, 2024)
The challenge of using patient-specific, autologous stem cell therapies in clinical settings is the need for advanced cell processing and expansion technologies. These include decentralized, small-scale manufacturing at the point of care in hospitals. The highest risk for contamination in cell-based therapy products comes from animal- and human-derived components such as serum, blood components, and growth factors. To mitigate the risk of adventitious microorganism contamination, preventive measures like size-exclusion virus removal filtration of cell media components can be employed. This article examines the impact of nanofiltration using nanocellulose-based virus clearance filter paper on the differentiation of human pluripotent stem cells into insulin-producing pancreatic islets (SC-islets). The cells were monitored for biomarkers using flow cytometry and immunohistochemistry along the 7-stage differentiation protocol. The produced SC-islets were evaluated functionally using low and high glucose stimulation under dynamic perifusion conditions. Pluripotent stem cells grown in culture media filtered through 20 nm cut-off nanocellulose filters showed similar expression of desired biomarkers at each stage compared to the control group. At the end of stage 7, SC-islets exhibited a rounded shape and strong expression of insulin, glucagon, and somatostatin in both the control and filtered media groups. The present study demonstrates that SC-islets differentiated with nanofiltered media were functional.